Research priorities for children’s cancer: a James Lind Alliance Priority Setting Partnership in the UK - Nigel J Hall; David Weller; Bob Phillips; Faith Gibson; Susie Aldiss; Rachel Dommett; Jessica Elizabeth Morgan; Alex Brownsdon; Helen Morris; Julia Chisholm; Sonia Malik; Jonathan Gower; et al. (BMJ Open)
Objectives To engage children who have experienced cancer, childhood cancer survivors, their families and professionals to systematically identify and prioritise research questions about childhood cancer to inform the future research agenda.Design James Lind Alliance Priority Setting Partnership.Setting UK health service and community.Methods A steering group oversaw the initiative. Potential research questions were collected in an online survey, then checked to ensure they were unanswered. Shortlisting via a second online survey identified the highest priority questions. A parallel process with children was undertaken. A final consensus workshop was held to determine the Top 10 priorities.Participants Children and survivors of childhood cancer, diagnosed before age 16, their families, friends and professionals who work with this population.Results Four hundred and eighty-eight people submitted 1299 potential questions. These were refined into 108 unique questions; 4 were already answered and 3 were under active study, therefore, removed. Three hundred and twenty-seven respondents completed the shortlisting survey. Seventy-one children submitted questions in the children’s surveys, eight children attended a workshop to prioritise these questions. The Top 5 questions from children were taken to the final workshop where 23 questions in total were discussed by 25 participants (young adults, carers and professionals). The top priority was ‘can we find effective and kinder (less burdensome, more tolerable, with fewer short and long-term effects) treatments for children with cancer, including relapsed cancer?’Conclusions We have identified research priorities for children’s cancer from the perspectives of children, survivors, their families and the professionals who care for them. Questions reflect the breadth of the cancer experience, including diagnosis, relapse, hospital experience, support during/after treatment and the long-term impact of cancer. These should inform funding of future research as they are the questions that matter most to the people who could benefit from research.